Desirable Meat: The Social Context of Meat Procurement at Albert Porter Pueblo, a Great House Community in the Central Mesa Verde Region. Issue 3 (3rd July 2019) - Badenhorst, Shaw; Driver, Jonathan C.; Ryan, Susan C.
Abstract : The Albert Porter Pueblo great house, located in the central Mesa Verde region, was surrounded by numerous residential structures during the Pueblo II and Pueblo III periods. Using a variety of exploitation measures of wild game and turkeys, we test three hypotheses to see if there are meaningful similarities or differences in the faunal assemblages from the great house and the domestic households that surrounded it. Although the great house was a unique and prominent architectural feature at Albert Porter Pueblo, the faunas from the great house are generally similar to those from surrounding structures. However, there is some evidence that more meat of cottontails and turkeys was consumed in the great house compared to domestic structures during Pueblo III. Overall, all members from Albert Porter had equal access to animal food and those used in rituals and ceremonies. We explore different interpretations of social organization suggested by faunal remains.